Theoretical Study of Oxygen Atom Adsorption on A Polycyclic Aromatic Hydrocarbon Using Density-Functional Theory - Mokhammad Fajar Pradipta; Harno Dwi Pranowo; Viny Alfiyah; Aulia Sukma Hutama (Indonesian Journal of Chemistry, 2021)
Potential energy curves (PECs) and energy profiles of atomic O attack on coronene as a model for graphene/graphitic surface and interstellar reaction surface have been computed at the unrestricted B3LYP/cc-pVDZ level of theory to elaborate on atomic O attack mechanism and chemisorption on coronene. The PECs were generated by scanning the O atom distance to the closest carbon atom on "top" and "bridge" positions in the coronene, while fully relaxed geometries in the triplet state were investigated to gain the energy profile. We found that the most favorable geometry as the final product was the chemically bound O on the "bridge" site in the singlet state with an interaction energy of –29.2 kcal/mol. We recommended a plausible mechanism of atomic O attack and chemisorption reaction on coronene or generally graphitic surface starting from the non-interacting O atom and coronene systems into the chemically bound O atom on coronene.